Effect of surface wettability on tribological properties of Al2O3/TiC ceramic under wet lubrication. Issue 18 (15th December 2019) - Ge, Dongliang; Deng, Jianxin; Duan, Ran; Li, Xuemu; Liu, Yayun; Yue, Hongzhi
Abstract: The effect of surface wettability on the friction properties of Al2 O3 /TiC ceramic was investigated to improve the friction and wear of Al2 O3 /TiC ceramic tool surfaces. The surface wettability of Al2 O3 /TiC ceramic was changed by preparing different microgroove arrays on its surface. The surface contact angles of the different samples were measured to characterize surface wettability. The reciprocating linear friction tests were implemented under liquid lubrication by a ball-disc type friction machine and the friction coefficient was measured. The worn surface characteristics of Al2 O3 /TiC ceramic were observed using SEM. Results showed that the surface wettability effectively improved the friction and wear properties of Al2 O3 /TiC ceramic. The friction coefficient of Al2 O3 /TiC ceramics decreased as surface wettability was enhanced. The surface wettability enhancement of 86.8% corresponds to a reduction in the friction coefficient of 73.6%. The better the wettability, the smoother the worn surface. The mechanism responsible was explained as micro-textures promoted capillary adsorption of lubricating fluid on the surface of Al2 O3 /TiC ceramic. The additional capillary adsorption force reduced the solid-liquid interfacial tension, thereby enhancing the surface wettability of the Al2 O3 /TiC ceramic, which promoted spreading ability of lubricating fluid. Therefore, the lubricating fluid can form a continuous lubricating film at the friction interface to achieve the effect of reducing the friction.